MAJU MUNDURNYA ISLAM DI SPANYOL - Sitti Aisyah (Rihlah : Jurnal Sejarah dan Kebudayaan, 2013)
This paper discusses Islam in Spain which is one of the historical evidence of Muslim rule. Spain is an Islamic territory conquered in 705 AD, during the reign of the Umayyads. The arrival of Islam in Spain is an event that greatly influenced the Islamic world in which he brought and opened the eyes of the Europeans who have provided its own nuances and invaluable contribution to both the Islamic world and the Western world, in terms of science and civilization. The progress brought and introduced Islam to the Western world is characterized by the emergence of figures scientists and philosophers of the country. Muslim rule in Spain which had reached its peak and then slowly destroyed due to various factors.